1974
DOI: 10.1139/v74-537
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Aqueous Solutions of Hydrogen Peroxide Containing β-Ammonio Alcohols

Abstract: During the photolysis of aqueous H2O2 added β-ammonio alcohols suffer oxidative attack initiated through hydrogen abstraction by the •OH radical. At pH 7.0 the initially formed radical,[Formula: see text] undergoes fragmentation to yield [Formula: see text] and CH3COR′ exclusively. At pH 1.0 fragmentation is less important and direct oxidation to [Formula: see text] dominates. A radical deprotonation step is proposed to account for the pH dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…This proposal draws support from radiolysis experiments in which choline-derived radicals undergo fragmentation very rapidly under neutral conditions (Foster and West, 1974). EPR studies of the substrate-based radical of TDP-D-quinovose generated by DesII have revealed the importance of establishing overlap between the partially filled p-orbital at the radical center and the σ * orbital of the adjacent functional group to be eliminated (Ruszczycky et al, 2011).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This proposal draws support from radiolysis experiments in which choline-derived radicals undergo fragmentation very rapidly under neutral conditions (Foster and West, 1974). EPR studies of the substrate-based radical of TDP-D-quinovose generated by DesII have revealed the importance of establishing overlap between the partially filled p-orbital at the radical center and the σ * orbital of the adjacent functional group to be eliminated (Ruszczycky et al, 2011).…”
Section: Discussionmentioning
confidence: 81%
“…Were migration of the trimethylammonium group key to catalysis (the EAL model), one would predict that residues that could facilitate this migration through direct contacts with the trimethylammonium moiety would be catalytically essential, as has been observed for ammonia migration in ethanolamine ammonia-lyase (Mori et al, 2014). Whereas a 1,2-migration reaction requires that exquisite control be exerted over the migrating group by active site residues, no such requirement is necessary for a 1,2-elimination; indeed, this reaction proceeds very rapidly in solution (Foster and West, 1974). Thus, the retention of activity for the Y208F/Y506F double mutant supports a 1,2-elimination mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The largest decrease in the absorbance intensity was observed for salt 2, which was most likely caused by the parallel photodegradation of L-histidine, 45,46 assuming that the other components did not photodegrade under the same conditions. 18,[47][48][49][50][51] Finally, the IBA biological activity was determined. Three concentrations of the active substance were used for biological tests (the methodology is described in the ESI †): the IBA concentration recommended by the manufacturer (50 mg L À1 ) and half and twice this concentration (25 mg L À1 and 100 mg L À1 , respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The radicals were formed from β-amino alcohols by the Ti(III)-H 2 O 2 oxidation 217 or photolysis in the presence of H 2 O 2 . 218 These rearrangements proceed under neutral conditions in the absence of Co-(II).…”
Section: A Model Studiesmentioning
confidence: 99%